The dilemma between economic motifs and social responsibility: goals ambiguity in government-owned enterprise / Rendy Billiyanto and Antun Mardiyanta - Billiyanto, Rendy; Mardiyanta, Antun (2021)
There is a significant part of the world’s economy controlled by public companies. Nevertheless, there remains a scarcity of information on how the interaction between economic (profit) motifs and social (service) goals is carried out by public companies. We address this issue by applying phenomenology research methods to obtain answers to such dilemmas in policy goals. This study focuses on the government-owned water treatment company (PDAM or Perusahaan Daerah Air Minum) by Surabaya Metropolitan government. We use a theoretical understanding of the goals ambiguity, goals conflict, and goals re-prioritization to understand the dilemma of policy goals.